Strategi Mengelola Keuangan Bagi Para Ibu Pelaku Usaha Kecil Di Kelurahan Rempoa Kecamatan Ciputat Timur - Andri Gunawan; Siti Marhamah; Ali Ma'sum (Prisani Cendekia, 2023)
A productive mother can also be interpreted as a mother who helps the family finances by running a small business. Every additional income earned will help the family economy to be better. The small entrepreneur mother is able to take advantage of the available free time, and the resources she has for doing business. Mothers who run small businesses mean realizing economic independence which has a broad social impact, for example a mother who has her own income will not depend on her husband's income, that if something happens a husband cannot generate income anymore, then a mother will be ready to face life's tests the. By cooperating with this PkM partner, the Rempoa Community Empowerment Institute. The PkM implementation method includes providing socialization on financial management to mothers of small business actors in Rempoa Village, so that the mothers of small business actors have a good financial management strategy, before the socialization is given, do preliminary test (pre-test) to determine the level of knowledge about small business financial management, and at the end of the training, it is tested again (post-test) to determine any changes in knowledge about small business financial management. The service activities went well, and the participants stated that the knowledge and knowledge provided was very useful, and from the results of the implementation evaluation, the participants stated that they would try to implement the financial knowledge provided by the Yarsi University Lecturers